2001
DOI: 10.1021/ja0111232
|View full text |Cite
|
Sign up to set email alerts
|

Weak Intramolecular Proton−Hydride and Proton−Fluoride Interactions:  Experimental (NMR, X-ray) and DFT Studies of the Bis(NBH3) and Bis(NBF3) Adducts of 1,3-Dimethyl-1,3-diazolidine

Abstract: Bis(NBH(3)), bis(NBF(3)), and NBF(3)/NBH(3) adducts 1-3 were prepared from 1,3-dimethyl-1,3-diazolidine and characterized by the (1)H, (13)C, (11)B, (19)F, 2D (1)H(-13)C HETCOR and NOESY NMR spectra. The structures and conformations of the adducts were established by the variable-temperature (1)H NMR spectra, the X-ray diffraction method (adduct 2A), and density functional calculations at different theoretical levels. The experimental and theoretical data have revealed that bis adducts 1-3 prefer trans orienta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…29) with BF 3 . 291 BF 3 has been used to model BH 3 in adducts of the fused carbocyclic azafenestranes to probe the effect of coordination of the amine N-donor atom on the planarity of the central quaternary C atom. These also incorporate distorted tetrahedral coordination.…”
Section: Boronmentioning
confidence: 99%
“…29) with BF 3 . 291 BF 3 has been used to model BH 3 in adducts of the fused carbocyclic azafenestranes to probe the effect of coordination of the amine N-donor atom on the planarity of the central quaternary C atom. These also incorporate distorted tetrahedral coordination.…”
Section: Boronmentioning
confidence: 99%
“…iiNMR measurements combined with DFT theoretical calculations have revealed the existence of intramolecular hydrogen bonds in organofluorine-substituted derivatives of different classes of molecules (ref (27)). In addition, it has been suggested that proton–fluoride interactions can play a significant role in the stabilization of conformational molecular states ,especially via cooperativity(ref (28))…”
mentioning
confidence: 99%
“…It has been demonstrated (theoretically and experimentally) that bis(NBH 3 ) and bis(NBF 3 ) adducts of 1,3-dimethyl-1,3-diazolidine exhibit weak proton-hydride and proton-fluoride interactions, respectively (see Scheme 12). Nevertheless, the weak interactions can play a significant role in the stabilization of conformational molecular states, especially when cooperativity is involved (119). Intramolecular contacts of the type C-H Recently, a strategy to measure the transfer rates within the 13 C Zeeman order was proposed; this approach considers the cross-correlated relaxation rates (CCRRs), the longitudinal and transversal relaxations, and the nOe in highly symmetric compounds (121).…”
Section: Breaking the Distance Limitmentioning
confidence: 99%
“…It has been demonstrated (theoretically and experimentally) that bis(NBH 3 ) and bis(NBF 3 ) adducts of 1,3-dimethyl-1,3-diazolidine exhibit weak proton-hydride and proton-fluoride interactions, respectively (see Scheme 12). Nevertheless, the weak interactions can play a significant role in the stabilization of conformational molecular states, especially when cooperativity is involved (119). Intramolecular contacts of the type C-H dþ ÁÁÁ dÀ H-B and C-H dþ ÁÁÁ dÀ F-B (2.2-2.5 Å ), which are established in some cyclic borane adducts in the solid state, can affect the conformational states of such molecules in solution (120).…”
Section: Scheme 11mentioning
confidence: 99%